'Facing the wrong way': Exploring the Occipito Posterior position/back pain discourse from women׳s and midwives perspectives. Issue 10 (October 2015) - Lee, Nigel; Kildea, Sue; Stapleton, Helen
Abstract Objective to explore back pain in labour from the perspectives of women and midwives. Design a qualitative study, which generated data through individual semi-structured interviews with postnatal women and focus groups with midwives. Data were analysed thematically. Setting two metropolitan maternity units in Queensland, Australia. Participants nine postnatal women and 11 midwives, all of whom had participated in a randomized controlled trial investigating the use of sterile water injections for back pain in labour. Findings two major themes were identified, including back pain in labour: accounts, rationalisations and coping strategies, and fetal position: destabilising the Occipito Posterior-back pain discourse. Key conclusions back pain may be severe in labour, may impact negatively upon women׳s labour and birth experiences, and interfere with their ability to cope as planned. The assumed relationship between fetal position and back pain in labour is a dominant discourse, albeit one which is lacking in empirical credibility. Nonetheless, the information provided to women by maternity professionals tended to reiterate customary practices and beliefs rather than factual knowledge. Increasingly, women refer to other sources, which may challenge the information provided by health professionals. Implications for practice: Back pain in labour is an under-researched area and the lack of solid evidence underpinning the advice provided to women has implications for labour management, and possibly for maternal and fetal outcomes. Care providers might usefully consider back pain as multifactorial, not always associated with OP position, and continue to seek evidence-based management strategies which address women׳s needs.